Health Impact of Occupational Exposure to Noise - A Mixed Method Assessment (Global Journal of Science Frontier Research, 2020)
Introduction: Globally, activities in the oil and gas industry are accomplished with the aid of machinery with the potentials to generate high noise levels above 85 dB(A). A visit to a typical crude oil production facility in Sub-Saharan Africa(SSA) revealed noise-producing machinery such as generators, compressors, pumps, fluid, and gas flow, to mention but a few. This study assessed the health risks of exposure to noise in an offshore crude oil installation in Nigeria.
Keywords: noise; exposure; crude oil; machines; health impact